Analysis of the Electric Power Distribution System Service Reliability Index at PLN Lancang Garam - Aslami, Muhammad Mirdasil; Sadrina, Sadrina; Fachri, Muhammad Rizal (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2024)
The level of electrical energy demand in an area reflects the welfare of that community. The greater the use of electrical energy, the higher the community's standard of living, followed by the public's critical attitude towards everything that happens and influences lives, including electricity services. Generally, a network's reliability level can be seen from the size of the SAIDI and SAIFI values on the PLN (state electricity company) side. The calculation and reliability analysis results of the Lhokseumawe ULP above show that the total SAIFI index value is 2.68 times/year. The SAIFI Rayon Lhokseumawe reliability index is categorized as reliable because its value does not exceed the standard set by PLN in SPLN 68-2 of 1986, namely 3.2 times/year. The total value of the SAIDI index is 45.30 hours/year. The Lhokseumawe Rayon SAIDI reliability index is categorized as unreliable because its value exceeds the standard set by PLN in SPLN 68-2 of 1986, namely 21 hours/year. There are certainly differences in infrastructure, electrical equipment, and number of customers in 1986 compared to current years; this has a different influence on electricity reliability values such as SAIDI and SAIFI.